Analisis Penerapan Budaya Sekolah 5S dan 5K dalam Membangun Karakter Siswa di SDN Lirboyo 2 Kota Kediri - Devina Alya Cahyaningrum; Alfi Laila; Tria Santi Rohmawati; Mia Febriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Elementary school education not only emphasizes academic learning but also plays an important role in shaping students’ character and positive habits. Character education at the elementary level is essential as it forms the foundation of students’ attitudes and behavior in daily life. One effort to strengthen character education is through the implementation of school culture, namely the 5S culture (Smile, Greet, Say Hello, Politeness, and Courtesy) and the 5K culture (Cleanliness, Beauty, Neatness, Safety, and Order). This study aims to analyze the implementation of the 5S and 5K cultures in building students’ character at SDN Lirboyo 2, Kediri City. The research used a qualitative descriptive approach involving the principal, teachers, and students as research subjects. Data were collected through observation of daily activities, interviews with school members, and documentation of school programs. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data collection, data reduction, data presentation, and conclusion drawing. Data validity was ensured through source and method triangulation. The results show that the implementation of the 5S and 5K cultures at SDN Lirboyo 2 has been well planned and consistently implemented. The 5S culture is reflected in polite behavior and respectful communication, while the 5K culture is evident through routine cleanliness and environmental management activities. Overall, the implementation of these cultures contributes positively to students’ discipline, responsibility, environmental awareness, and courteous behavior, supporting effective character education in elementary schools.